Muhammadiyah’s Religious Ideology and the Challenges of Transnationalism in Islamic Religious Education in Indonesia - Nurul Hidayah; Faridi Faridi; Hikmatulloh Hikmatulloh (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
The growing influence of transnational Islamic movements on Islamic Religious Education (PAI) in Indonesia has emerged as a new challenge for local religious organizations such as Muhammadiyah. This study aims to explore how Muhammadiyah, as a modernist Islamic movement, responds to transnational religious ideologies within the educational domain. Employing a qualitative approach through literature review, this research analyzes scholarly articles, major books, and official Muhammadiyah documents. The findings indicate that Muhammadiyah actively defends its progressive Islamic ideology through strategies such as strengthening higher education, internationalizing institutions, and revitalizing cadre development. Muhammadiyah’s ideological stance, rooted in wasathiyah (moderation) and inclusivity, is pivotal in countering the infiltration of transnational ideologies, which tend to be radical and intolerant. This study underscores the importance of reinforcing PAI curricula based on moderate Islamic values as a strategic step in preserving national Islamic identity.